(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article is devoted to the study of feelings and emotions from both linguistic and psychological perspectives. The research addresses the problem of terminological ambiguity surrounding such related concepts as feeling, emotion, and emotionality, which remain insufficiently differentiated in modern humanities. Relying on the works of prominent scholars including N. V. Avanesova, D. P. Sedykh, V. I. Shakhovsky, W. McDougall, and A. Damasio, the article examines the nature, classification, and universal character of human feelings and emotions. Special attention is paid to the ways feelings and emotions are verbalized in language. The study identifies the main linguistic methods of expressing emotional states, such as direct nomination, expressive means, and descriptive representation of feelings through verbal and non-verbal features. The article also distinguishes between the lexicon of feelings and emotional lexicon, emphasizing the expressive and evaluative character of the latter. The findings highlight the necessity of an interdisciplinary approach to the study of emotional phenomena and confirm the absence of a unified terminological framework in the analysis of feelings and emotions within linguistics.